2020
DOI: 10.1111/pde.14214
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic conditions in Down syndrome: A single‐center retrospective chart review

Abstract: Background: Current literature addressing dermatologic conditions associated with Down syndrome is limited, with emphasis on rare skin conditions and lack of consensus on the incidence of more common disorders. Objective: We sought to evaluate dermatologic conditions in patients with Down syndrome diagnosed and managed by dermatologists. Methods: This was a retrospective analysis of 101 pediatric and adult patients with Down syndrome seen by the University of Massachusetts Dermatology Department between 2008 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
(51 reference statements)
1
21
0
1
Order By: Relevance
“…Follicular occlusion disorders, including folliculitis and hidradenitis suppurativa, are among the most common cutaneous conditions in patients with DS. [22][23][24][25][26][27][28] Folliculitis was first described as Pityrosporum folliculitis on the chest and back. 29,30 Recent publications have described a refractory inflammatory folliculitis concentrated on the thighs and buttocks that can result in anetoderma-like scar formation (Figure 1A,1B).…”
Section: Adnexal Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Follicular occlusion disorders, including folliculitis and hidradenitis suppurativa, are among the most common cutaneous conditions in patients with DS. [22][23][24][25][26][27][28] Folliculitis was first described as Pityrosporum folliculitis on the chest and back. 29,30 Recent publications have described a refractory inflammatory folliculitis concentrated on the thighs and buttocks that can result in anetoderma-like scar formation (Figure 1A,1B).…”
Section: Adnexal Conditionsmentioning
confidence: 99%
“…29,30 Recent publications have described a refractory inflammatory folliculitis concentrated on the thighs and buttocks that can result in anetoderma-like scar formation (Figure 1A,1B). 22,24,27,28,31 Several studies have found this form of folliculitis to be the most common skin diagnosis, and many patients have a concomitant diagnosis of HS, suggesting these conditions may be along the same continuum. 22,24,27,28 Hidradenitis suppurativa appears to be more prevalent in DS (Figure 1C,1D).…”
Section: Adnexal Conditionsmentioning
confidence: 99%
See 3 more Smart Citations